Facile fabrication of YSZ/GDC multi-layers by using a split target in pulsed laser deposition and their structural and electrical properties - Park, Jung Hoon; Hong, Wan-Shick; Lee, Jong-Ho; Yoon, Kyung Joong; Kim, Hyoungchul; Hong, Jongsup; Song, Hue-Sup; Son, Ji-Won (SPRINGER, 2014)
Various configurations of the multi-layer of yttria-stabilized zirconia (YSZ) and gadolinia-doped ceria (GDC) are successfully fabricated through a novel method by means of pulsed laser deposition (PLD) utilizing a split target. By controlling the deposition conditions like the laser frequency and target configuration, YSZ/GDC multi-layers of different periodicities and YSZ/GDC thickness ratios can be easily and simply realized. The multi-layer fabricated by the proposed method exhibits nearly identical physical and electrical properties to those of the multi-layer films by the conventional layer-by-layer deposition method. The present study provides a facile and effective fabrication method for the design and application of multi-layered structure.
Keywords: FAST-ION CONDUCTION; TEMPERATURE; ELECTROLYTE; FILMS; INTERFACES; TRANSPORT